Bevaring av bygningsmiljøer. Et historisk tilbakeblikk på noen norske bevaringsområder - Sognnæs, Johanne (Nordlit, 2015)
After the overall city redevelopments after World War II, the dominant view concerning the so-called “living city” is that it must actively pursue both conservation and renewal. Urban development is about taking care of existing qualities and simultaneously creating new ones. How this should be handled in practice, however, is under continuous debates both within academic communities and beyond. Antiquarians and architects have in some periods and specific cases disagreed, in other instances, however, they have cooperated. This article presents a historical retrospective of some of the main issues of the conservation debates in Norway. What were the reasons for protection and which issues were put into focus? How strong was the protection, and what kind of renewals were accepted? These questions are discussed with reference to, among others, the examples of Gamle Stavanger [Old Stavanger], “Posebyen” in Kristiansand and Lærdalsøyri by the Sogne fjord. The essay also considers some of the central terms at work in the discussions of architectural and urban developments, such as “building character”, legibility, authenticity, adaptation and contrast.